Recognition of Core‐ and Polymerase‐derived immunogenic peptides included in novel therapeutic vaccine by T cells from Chinese chronic hepatitis B patients. (29th October 2017) - Huang, D.; Sansas, B.; Jiang, J. H.; Gong, Q. M.; Jin, G. D.; Calais, V.; Yu, D. M.; Zhu, M. Y.; Wei, D.; Zhang, D. H.; Inchauspé, G.; Zhang, X. X.; et al.
Summary: Chronic hepatitis B (CHB) is one of the major public health challenges in the world. Due to a strong interplay between specific T‐cell immunity and elimination of hepatitis B virus (HBV), efforts to develop novel immunotherapeutics are gaining attention. TG1050, a novel immunotherapy, has shown efficacy in an animal study. To support the clinical development of TG1050 in China, specific immunity to the fusion antigens of TG1050 was assessed in Chinese patients. One hundred and thirty subjects were divided into three groups as CHB patients, HBV spontaneous resolvers, and CHB patients with HBsAg loss after antiviral treatment. HBV‐specific T‐cell responses to pools of HBV Core or Polymerase genotype D peptides included in TG1050 were evaluated. HBV Core‐ or Polymerase‐specific cells were detected in peripheral blood mononuclear cells (PBMCs) from the different cohorts. The frequencies and intensities of HBV Core‐specific immune responses were significantly lower in CHB patients than in HBsAg loss subjects. In CHB patients, a dominant pool derived from Polymerase (Pol1) was the most immunogenic. CHB patients with low viral loads (<10 6 IU/mL) were more likely to have a positive response specific to the Core peptide pool. Overall, genotype D‐derived peptides included in TG1050 could raise broad and functional T‐cell responses in PBMCs from Chinese CHB patients infected with genotype B/C isolates. Core‐specific immunogenic domains appeared as "hot spots" with the capacity to differentiate between CHB vs HBsAg loss subjects. These observations support the extended application and associated immune monitoring of TG1050 in China.